Organization of effective accounting in a small enterprise - A. Y. Yanchenko; A. V. Semkovskaya (Путеводитель предпринимателя, 2024)
The article is devoted to the organization of accounting in small enterprises. Proper and effective organization of accounting is of great importance for the development and existence of each enterprise. Choosing the right accounting methods suitable for a particular organization, which take into account all its features of functioning and the specifics of its activities, provide the company with reliable information on the basis of which management decisions are made that are important for the further functioning and development of the enterprise, as well as accounting (financial) statements are compiled. The article provides recommendations on the organization of accounting for small organizations. These include the reasonable choice of the person who is responsible for accounting, the choice of the form of its management, the use of an abbreviated chart of accounts, which groups accounting accounts into enlarged groups, as well as the use of the cash method and the use of abbreviated reporting forms. All the recommendations presented in the article allow you to collect information about the state and movement of accounting objects more quickly and in the most convenient way, as well as reduce the intensity of the accountant’s work.